Implementasi Pelatihan dan Pendampingan Kelas Inklusif Digital untuk Guru Sekolah Dasar - Wayan Eka Paramartha; Ni Made Daini Vitri Sinta Sari; Muhammad Idris (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2026)
Purpose –This community service program aims to enhance teachers’ competencies in managing inclusive classrooms and to strengthen learning strategies through a digital-based approach. Design/methodology/approach – The method used was a participatory design involving training, mentoring, workshops, and classroom practice. Data were collected using post-tests, observations, and documentation of learning products. Findings – The results show a significant improvement in teachers’ managerial competencies, where skills in developing digital modules, interactive quizzes, and adaptive assessments increased up to 85%. In the social aspect, teachers’ interaction skills rose to 90%, while parental involvement in supporting inclusive education increased to 82%. Originality/value – These findings indicate that the program not only enhanced teachers’ individual capacity but also built collective empowerment within the school ecosystem. In conclusion, the integration of digital innovation and social collaboration effectively strengthened inclusive practices, improved school empowerment levels, and created a sustainable model for inclusive education.